Analisis Bibliometrik Penggunaan Video Pembelajaran di Sekolah Dasar Tahun 2013-2022 Menggunakan Aplikasi VOSViewer - Fitri Indriyanti; Tia Nurul Fauziah; Asep Nuryadin (Universitas Majalengka, 2023)
This study aims to analyze the use of instructional videos in elementary schools between 2013 and 2022 using the bibliometric computational mapping analysis method. The Publish or Perish software was used to collect publications data from the Google Scholar database using the keywords